The Effect Of Promotion On Sales Of Sport Utility Vehicle Cars - Maulidina, Maulidina (Jurnal Ekonomi, 2024)
Sports Utility Vehicle (SUV) cars are increasingly in demand by the public. SUVs are a type of car that combines two types of car, namely passenger and off-road. With this combination, the SUV can not only be driven on ordinary urban roads, but also on rough terrain such as rocky roads, many people use this type of car. This research discusses the influence of promotions on sales of Sport Utility Vehicle (SUV) cars at PT. Pahala Automotive International Dipo, which is limited to the Pajero car type. The purpose of this research is to determine the effect of promotions on company sales at PT. Automotive Pahala International Dipo. Where within a period of 6 (six) months there was fluctuation in sales of Pajero type cars. This research has 2 (two) variables, namely Promotion (Variable And Sales (Variable Y) with its indicators (increasing and deeper curiosity about the product and its advantages to find out more easily). This research used quantitative methods and a population of 43 respondents, and a sample of 43 respondents. This research uses a questionnaire to collect data from respondents. The results of this research shown by the Multiple Linear Regression Analysis model are Y = 7,749 + 12,898 (X). With the large influence of promotion through the coefficient of determination test of 0.797 or 79.7% while the remaining 20.3% is influenced by other variables. Based on the results of this research, the promotion variable is a variable that influences sales at PT. Dipo Internasional Pahala Automotive is proven by the results of the promotional t test which has an influence on sales.